Lumbrical Muscles Neural Branching Patterns: A Cadaveric Study With Potential Clinical Implications. (September 2022) - Colonna, Michele R.; Piagkou, Maria; Monticelli, Andrea; Tiengo, Cesare; Bassetto, Franco; Sonda, Regina; Battiston, Bruno; Titolo, Paolo; Tos, Pierluigi; Fazio, Antonina; Costa, Alfio Luca; Galeano, Mariarosaria; et al.
Background: Lumbrical muscles originate in the palm from the 4 tendons of the flexor digitorum profundus and course distally along the radial side of the corresponding metacarpophalangeal joints, in front of the deep transverse metacarpal ligament. The first and second lumbrical muscles are typically innervated by the median nerve, and third and fourth by the ulnar nerve. A plethora of lumbrical muscle variants has been described, ranging from muscles' absence to reduction in their number or presence of accessory slips. The current cadaveric study highlights typical and variable neural supply of lumbrical muscles. Materials: Eight (3 right and 5 left) fresh frozen cadaveric hands of 3 males and 5 females of unknown age were dissected. From the palmar wrist crease, the median and ulnar nerve followed distally to their terminal branches. The ulnar nerve deep branch was dissected and lumbrical muscle innervation patterns were noted. Results: The frequency of typical innervations of lumbrical muscles is confirmed. The second lumbrical nerve had a double composition from both the median and ulnar nerves, in 12.5% of the hands. The thickest branch (1.38 mm) originated from the ulnar nerve and supplied the third lumbrical muscle, and the thinnest one (0.67 mm) from the ulnar nerve and supplied the fourth lumbrical muscle. In 54.5%, lumbrical nerve bifurcation was identified. Conclusion: The complex innervation pattern and the peculiar anatomy of branching to different thirds of the muscle bellies are pointed out. These findings are important in dealing with complex and deep injuries in the palmar region, including transmetacarpal amputations.